Efficacy of Carbofuran in Controlling Root-Knot Nematode (Meloidogyne javanica Whitehead, 1949) on Cultivars of Bambara Groundnut (Vigna subterranea (L.) Verdc.) in Yola, Nigeria - M. Y. Jada; D. T. Gungula; I. Jacob (International Journal of Agronomy)
Bambara groundnut (Vigna subterrenea L. Verdc.) is an important crop produced in Adamawa State of Nigeria. However, the production of the crop is seriously threatened by root-knot nematodes (RKNs; Meloidogyne spp.). Since cultural methods have not been very effective in controlling RKN, carbofuran was evaluated to determine its efficacy in controlling M. javanica in Yola during 2002 and 2003. Three bambara groundnut cultivars (Kwachanjiwa, Kwaheuma, and Kwatolotolo) were evaluated using three application timings (at planting, 3 and 6 weeks after planting, and none). Results indicated that applying carbofuran at planting provided the greatest reduction in M. javanica population levels, which lead to increased yields in bambara groundnuts compared to the other two application timings. Furthermore, both Kwachanjiwa and Kwatolotolo provided similar high yields compared to Kwaheuma, which was most likely related to the M. javanica tolerance in these cultivars.